2018
DOI: 10.1155/2018/1920198
|View full text |Cite
|
Sign up to set email alerts
|

Antistaphylococcal and Antibiotic Resistance Modulatory Activities of Thirteen Cameroonian Edible Plants against Resistant Phenotypes

Abstract: Background In this study, 18 methanol extracts from Cameroonian edible plants were tested for their antibacterial activities against 26 strains of S. aureus; the role of efflux pumps in the resistance of tested bacteria and the antibiotic resistance-modulating activities against selected multidrug-resistant (MDR) phenotypes were also investigated. Methods Broth microdilution assay was used to evaluate the antibacterial activity, the role of efflux pumps, and the antibiotic resistance-modulating effects of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Secondary metabolites contained in plants due to their multiple biological activities are increasingly the preferred target in the scientific community's search for new and effective drug substances (Cowan, 1999). Several scientific studies have demonstrated the pharmacological properties of a number of medicinal and edible plants (Wamba et al, 2018;Bobasa et al, 2018;Mbaveng et al, 2018). However, only a few studies published have investigated the in vivo toxicity of food spices.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites contained in plants due to their multiple biological activities are increasingly the preferred target in the scientific community's search for new and effective drug substances (Cowan, 1999). Several scientific studies have demonstrated the pharmacological properties of a number of medicinal and edible plants (Wamba et al, 2018;Bobasa et al, 2018;Mbaveng et al, 2018). However, only a few studies published have investigated the in vivo toxicity of food spices.…”
Section: Introductionmentioning
confidence: 99%
“…Although the S. mombin leaves was not recorded in this study, tests indicate antibacterial (BRITO et al, 2018c;WAMBA et al, 2018), antidiabetic (GOODIES et al, 2015, uterine contraction-inducing (PAKOUSSI et al, 2018) and antioxidants (OJO et al, 2018) from compounds extracted from this organ. This plant is frequently cited in the treatment of malaria in several indigenous groups in the Amazon (CARABALLO et al, 2004;RUIZ et al, 2011; and also in Africa (IDOWU et al, 2010;KOUDOUVO et al, 2011;TRAORÉ et al, 2013;YETEIN et al, 2013), and its phytochemistry has been extensively investigated, revealing terpenes, phenols, tannins, saponins, flavonoids, alkaloids and sterols as important constituents of the various parts of this plant (HAMANO; MERCADANTE, 2001;VASCO et al, 2008;TIBURSKI et al, 2011;ASUQUO et al, 2013;LOURENÇO et al, 2018).…”
Section: Spondias Dulcismentioning
confidence: 72%
“…As a result, the treatment significantly reduced the mouse pathogenic conditions by 80 and 60%, 80 and 80%, and 60 and 40% for the aqueous, methanol, and hexane extracts, respectively [43] (Table 6). Wamba et al [44] demonstrated the anti-staphylococcal activity of the methanol extract of Irvingia gabonensis leaves against seven (7) clinical isolates, namely SA18, SA23, SA56, SA116, MRSA3, MRSA9, and MRSA11, with an MIC value of 1024 µg/mL [44]. In addition, Olanrewaju et al [13] assessed the antibacterial activity of the chloroform extract of I. gabonensis leaves against a series of bacteria (Salmonella typhi, Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa) and fungi (Trichophyton rubrum and Candida albicans).…”
Section: Antimicrobial Activitymentioning
confidence: 99%